Redefinition of human-centric skills in language education in the AI-driven era - Qassrawi, Rania; Al Karasneh, Samih Mahmoud (Universitas Syiah Kuala, 2025)
The widespread use of Artificial intelligence (AI) in language education has opened up a new era of teaching and learning, raising concerns about balancing AI-driven instruction and conventional teaching methods to achieve optimal learning outcomes while preserving essential human skills. Hence, this meta-analysis study systematically presented the findings from 60 studies conducted between 2018 and 2024, exploring the role of AI applications in language teaching. We investigated language skills and domains that AI can enhance, including skills (i.e., listening, speaking, reading, and writing), translation and interpretation, and teaching pedagogy and methods, alongside the human-centric skills that AI cannot replicate in language education. Based on the findings, AI could make significant strides in improving language proficiency, particularly in areas such as pronunciation, conversational fluency, grammar, and vocabulary. It can also assist in streamlining teaching methods, such as adaptive learning, automated assessment, and personalized content creation. However, some limitations emerged from the data. While AI excels at providing objective feedback and supporting innovative teaching methods, it struggles to cultivate essential human skills like cultural sensitivity, emotional intelligence, and critical thinking. These skills are necessary for effective communication, building relationships, and understanding language tones in different contexts. The study concluded that AI can be a powerful tool for language education but cannot replace human educators. Instead, language teaching practices should bridge a balance between AI-powered instruction and traditional teaching methods, so learners can benefit from the latest technological advancements while still developing the critical human skills they need in this ever-changing world.